An evaluation of quality of life (OHIP-14) in facial adenocarcinoma patient with adjuvant therapy: case report: Evaluasi kualitas hidup (OHIP-14) pada pasien adenokarsinoma wajah dengan terapi adjuvant: laporan kasus - Agustin Ninintowe T. Santo; Tenny Setiani Dewi; Eka Marwansyah Oli'i; Fika Faradillah Drakel (Makassar Dental Journal, 2022)
Adenocarcinoma is a type of carcinoma that begins from the glands. Impovement in management of head and neck cancer have resulted in decreased mortality, increased survival rates and patient’s quality of life. The World Health Organization defines quality of life are include three things, physical function, mentalstatus and ability to socially interact. It is reported a 19-year-old male with a history of right infraorbital adenocarcinoma who had undergone hemimaxillectomy,chemotherapy and radiotherapy. The patient complains painful swallowing and soreness in the oral cavity. Extraoral examination face and eyes was asymmetrical,there was keloid tissue in the right infraorbital and dry lips. Intraoral examination found white plaque on the upper labial mucosa, the left buccal mucosa had severalerythematous lesions and brownish macules. Yellowish white plaque on the anterior two-third of the tongue’s dorsum and there are fissures. Necrotic area on ​​right hard palate with yellowish margin. The teeth at first region are edentulous, whereas regions 2, 3 and 4 most of them are radix. The patient’s quality of life was assessed using the oral health impact profile (OHIP-14). Based on the assessment, the patient's quality of life at the first visit was poor with score 45, the next visit showed improvement with score 39, reduced in pain, improved physical and psychological abilities. It s concluded that oral and dental health is an important thing that can improve the quality of life of patients with infraorbital adenocarcinoma which is supported by good communication between doctors and patients.